2014
DOI: 10.1136/amiajnl-2014-002702
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying care coordination using natural language processing and domain-specific ontology

Abstract: 'Communicate' and 'manage' activities are widely used in care coordination. This confirmed the expert hypothesis that nurse care coordinators spent most of their time communicating about their patients and managing problems. Overall, nurses performed care coordination in both AIP and HHC, but the aggregated dose across Omaha problems and categories is larger in AIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…Prior studies using NLP include ones examining documentation of postoperative complications, colonoscopy quality measures, and influenza surveillance . A recent study reported the use of NLP to assess a range of care coordination activities that home health nurses documented in an EMR, including case management and medication counseling, but no prior study has used NLP to assess the success of communication between clinicians . NLP could be a valuable tool for future efforts in research and clinical quality improvement to document and analyze data related to care coordination and communication between clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies using NLP include ones examining documentation of postoperative complications, colonoscopy quality measures, and influenza surveillance . A recent study reported the use of NLP to assess a range of care coordination activities that home health nurses documented in an EMR, including case management and medication counseling, but no prior study has used NLP to assess the success of communication between clinicians . NLP could be a valuable tool for future efforts in research and clinical quality improvement to document and analyze data related to care coordination and communication between clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐centred care at home is a complex issue, and to ensure that patients’ needs are met, a comprehensive professional competence framework that incorporates the coordination of multiple systems and intra‐ and interprofessional collaboration is needed (Larsen, Broberger, & Petersson, ; Vaartio‐Rajalin et al, ). Care coordination is essential to healthcare reforms aiming to reduce healthcare costs and improve patients’ experiences of care quality (Popejoy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The standardized nursing terminology adopted in this study (i.e., Omaha System) was conducive in quantifying patterns of nursing interventions provided over the one year of care coordination services as demonstrated in previous studies. 4649 …”
Section: Discussionmentioning
confidence: 99%